High frequency of secondary, but not primary ocular manifestations of inflammatory bowel disease in patients treated at a tertiary care center. Issue 12 (December 2018) - Walldorf, Jens; Twarz, Maria; Schober, Celestina; Michl, Patrick; Hammer, Thomas
Abstract : Objective: Ocular manifestations of inflammatory bowel disease (IBD) are relevant complications of IBD. Only a few prospective studies are available on the characteristics of these manifestations. The aim of this study was to characterize the frequency of eye disease in patients with IBD, including primary and secondary ocular manifestations of IBD, and to identify patients who may need specialized ophthalmologic care. Patients and methods: In a prospective observational study, patients with IBD were examined for ocular symptoms in comparison with control participants without IBD. All patients with IBD underwent a thorough ophthalmologic examination (including slit-lamp, tonometry, tear breakup time, Schirmer's test, and coherence tomography). The results were analyzed with respect to sociodemographic and disease-related characteristics. Results: A total of 61 patients (33 women, 39 Crohn's disease, 22 ulcerative colitis, age 43.3±12.9 years, disease duration 12.4±9.3 years) were included. Ophthalmologic symptoms were reported by 53 patients (86.9%, most frequently deterioration of vision 42.6%, foreign body sensation 36.1%) compared with 60.6% in healthy controls ( P =0.001). A clinically relevant, previously undetected ophthalmologic diagnosis was identified in 56 patients (91.8% – dry eye syndrome 75.4%, cataract 67.2%, blepharitis 45.9%, fundus hypertonicus 14.8%, other 16.4%). Conclusion: Although primary ocular manifestations of IBD are rare in intensively treated patients, the high frequency of unrecognized secondary manifestations should give reason to refer especially patients with longstanding or complicated IBD to an eye specialist – irrespective of ocular symptoms.